UTM security with Fortinet : Mastering FortiOS - Tam, Kenneth (Syngress, 2013)
Traditionally, network security (firewalls to block unauthorized users, Intrusion Prevention Systems (IPS) to keep attackers out, Web filters to avoid misuse of Internet browsing, and antivirus software to block malicious programs) required separate boxes with increased cost and complexity. Unified Threat Management (UTM) makes network security less complex, cheaper, and more effective by consolidating all these components. This book explains the advantages of using UTM and how it works, presents best practices on deployment, and is a hands-on, step-by-step guide to deploying Fortinet's FortiGate in the enterprise. Provides tips, tricks, and proven suggestions and guidelines to set up FortiGate implementationsPresents topics that are not covered (or are not covered in detail) by Fortinet's documentation Discusses hands-on troubleshooting techniques at both the project deployment level and technical implementation area.
Keywords: Computer networks -- Security measures.; Computer networks -- Access control.; elektronické knihy; electronic books